Comparison of biogas production from an advanced micro-bio-loop and conventional system. (1st April 2017) - Jin, Qiang; Yang, Yan; Li, Aimin; Liu, Fuqiang; Shan, Aidang
Abstract: Biogas presents a most promising opportunity to reduce the world's dependence on fossil-fuel. The authors proposed an advanced micro-bio-loop (AMBL) to produce a continuous stream of biogas without requiring any additional external input or producing any internal output to its surroundings. The aim of this study was to compare biogas production from AMBL against that of a conventional biogas production system (CBPS) from the perspective of Life Cycle Sustainability Assessment (LCSA). The results indicated that the AMBL was much more energy-efficient and more technologically, environmentally, and sustainably advanced than an equivalent CBPS. The cumulative energy demands of both systems were at two different levels, 77.24 MJ and 130.45 MJ per functional unit respectively. All environmental impacts and total investment of the AMBL were 61% less than that of CBPS. Furthermore, abiotic depletion, eutrophication and ozone layer depletion of the former were merely 0.03%, 0.5% and 1% as compared to the latter respectively. Highlights: An advanced micro-bio-loop was proposed to produce biogas from biomass. The advanced micro-bio-loop was compared with conventional biogas production system. Significant improvements of the micro-bio-loop were proposed and discussed. The advanced micro-bio-loop can beat conventional biogas production system.